Force Analysis of a Circular Cylinder at Ununiformed Flow in a T Pipe Junction - Yantao Yin; Shicong Li; Liangbi Wang; Mei Lin; Qiuwang Wang (Energies, 2018)
Experimental and numerical investigations of force analysis acted on single circular cylinder in the T pipe junction with the effect of vanes are reported in this paper. Experiments are carried on in a small wind tunnel at five different velocity ratios (R) from 0.117 to 0.614. The mean pressure data acted on the cylinder are obtained and in turn the drag and lift. Vanes are installed at the junction to change the secondary flow in the branch duct and the angle is in the range of 90° ≤ φ ≤ 130°. Numerical studies which are validated by the experimental data help understand the flow structure for the analysis. It is found that in the T shape junction without vanes, the cylinder presents different surface mean pressure distributions at the different positions in the suction duct. As the increase of the distance from the junction to the cylinder center, the surface mean pressure distributions recover to the benchmark gradually which performs in the straight duct beforehand. Four feature points including the front/rear stagnation points and the separation points and the corresponding three divisions of flow region are analyzed in detail with the auxiliary numerical simulation of flow structure. Effect of the vanes with different angle is also discussed. Finally, the drag and lift coefficients acted on the cylinder with or without vanes are performed.